The Strategy of Interpretation Al Qur'an and Hadith with Virtual Data-Based Learning Approach at Institut Agama Islam Negeri Fattahul Muluk Papua - Syaiful Muhyidin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
The article gained experience through interviews with six academics from Institut Agama Islam Negeri Fattahul Muluk Papua through the voices of academics, gained the understanding and experience of using virtual data to understand the Al-Quran and Hadith. The data was processed by using a phenomenological approach involved data coding, evaluation, and drawing relevant conclusions. The result showed that the strategy of interpreting the Qur'an and Hadith by relying on virtual data as part of a learning approach in the 21st-century has illustrated how important it is to understand both Arabic as a foreign language, technology applications to interpret religious content, especially the Quran and Hadith. The transformation of the writing of the Qur'an from printing on paper has also been transformed into virtual data and followed by an interpretation by digital methods. It was one of the developments in the interpretation study methodology, considering that virtual data has entered various aspects of life, including the world of education and research. Keywords: Strategy Interpretation Al-Quran, Strategy Interpretation Hadith,Virtual Data Learning